PEMBERDAYAAN PETERNAK MELALUI PENYUNTIKAN VITAMIN B KOMPLEKS PADA SAPI DI DESA MALEALI KECAMATAN SAUSU KABUPATEN PARIGI MOUTONG - Eko Nurcahyo; Uti Nopriani; Burhanudin Burhanudin; Yusri Ramadhan Tuka; Indra Hutama Putra (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Farmer empowerment activities by students and lecturers of Sintuwu Maroso Poso University in the form of livestock health services aimed at increasing the empowerment of farmers in Maleali Village, Parigi Moutong Regency. This community service specifically aims to carry out the injection of vitamin B complex in cattle. Based on the observations of the service team from Sintuwu Maroso Poso University, most of the people in Maleali Village make a living as rancher farmers. The obstacle is the lack of knowledge of breeders about applied technologies in the field of animal husbandry, especially in the injection of B-complex vitamins in livestock. For this reason, the service team is trying to be a motivator and facilitator to optimize community empowerment in Maleali Village. With the knowledge possessed by the service team, it can be used to solve problems that have been faced by breeders. The implementation method is in the form of observation, counseling and evaluation. The results of this service show that the empowerment activity has a very positive impact, where breeders experience an increase in satisfaction with all stages of community service activities that have been carried out. The increase in farmer satisfaction is evidenced by the percentage of satisfaction survey results, namely 75% are very satisfied with the implementation of community service activities, 88% are very satisfied with the service of injecting vitamin B complex in cows, 94% are very satisfied with the answers given by the service team above the farmer's questions. The follow-up to this service is the need for facilities from the local village government and the Livestock and Animal Health Office of Parigi Moutong Regency.